Comprehensive in‐hospital monitoring in acute heart failure: applications for clinical practice and future directions for research. A statement from the Acute Heart Failure Committee of the Heart Failure Association (HFA) of the European Society of Cardiology (ESC). (30th April 2018) - Harjola, Veli‐Pekka; Parissis, John; Brunner‐La Rocca, Hans‐Peter; Čelutkienė, Jelena; Chioncel, Ovidiu; Collins, Sean P.; De Backer, Daniel; Filippatos, Gerasimos S.; Gayat, Etienne; Hill, Loreena; Lainscak, Mitja; Lassus, Johan; et al.
Abstract : This paper provides a practical clinical application of guideline recommendations relating to the inpatient monitoring of patients with acute heart failure, through the evaluation of various clinical, biomarker, imaging, invasive and non‐invasive approaches. Comprehensive inpatient monitoring is crucial to the optimal management of acute heart failure patients. The European Society of Cardiology heart failure guidelines provide recommendations for the inpatient monitoring of acute heart failure, but the level of evidence underpinning most recommendations is limited. Many tools are available for the in‐hospital monitoring of patients with acute heart failure, and each plays a role at various points throughout the patient's treatment course, including the emergency department, intensive care or coronary care unit, and the general ward. Clinical judgment is the preeminent factor guiding application of inpatient monitoring tools, as the various techniques have different patient population targets. When applied appropriately, these techniques enable decision making. However, there is limited evidence demonstrating that implementation of these tools improves patient outcome. Research priorities are identified to address these gaps in evidence. Future research initiatives should aim to identify the optimal in‐hospital monitoring strategies that decrease morbidity and prolong survival in patients with acute heart failure.